2018
DOI: 10.31728/jnn.2018.00022
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds: Incidence, Imaging Characteristics, Common and Uncommon Causes

Abstract: Cerebral microbleeds (CMBs) are considered as a marker of cerebral microangiopathy. CMBs can be detected in various clinical conditions, with the most common being cerebral amyloid angiopathy and chronic hypertension. Uncommon causes of CMBs include cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, Moyamoya disease, Fabry disease, fat embolism, infective endocarditis, prosthetic heart valves, posterior reversible encephalopathy syndrome, brain radiation, cocaine abuse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Susceptibility-weighted imaging (SWI) is a recently introduced magnetic resonance imaging (MRI) technique that provides improved detection of substances that cause susceptibility effects, such as iron, blood products, calcification, and air [ 1 ]. Studies have shown the superiority of SWI when compared with T2* for the detection of microsusceptibility changes in the brain, such as microhemorrhages in microangiopathy, moyamoya syndrome, angiitis, diffuse axonal injury, anticoagulant therapy, cerebral amyloid angiopathy, Fabry disease, embolism, brain radiation, and posterior reversible encephalopathy syndrome (PRES) [ 2 , 3 ]. Cerebral microbleeds (CMBs) are small-sized (less than 10 mm in diameter), focal, perivascular, hemosiderin depositions that are detected as round or ovoid, SWI-hypodense foci within the cerebral parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility-weighted imaging (SWI) is a recently introduced magnetic resonance imaging (MRI) technique that provides improved detection of substances that cause susceptibility effects, such as iron, blood products, calcification, and air [ 1 ]. Studies have shown the superiority of SWI when compared with T2* for the detection of microsusceptibility changes in the brain, such as microhemorrhages in microangiopathy, moyamoya syndrome, angiitis, diffuse axonal injury, anticoagulant therapy, cerebral amyloid angiopathy, Fabry disease, embolism, brain radiation, and posterior reversible encephalopathy syndrome (PRES) [ 2 , 3 ]. Cerebral microbleeds (CMBs) are small-sized (less than 10 mm in diameter), focal, perivascular, hemosiderin depositions that are detected as round or ovoid, SWI-hypodense foci within the cerebral parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some uncommon causes of CMB formation were not uncovered in our case series, such as amyloid angiopathy, anemia, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, or Fabry's disease. 4 In previous research, [18][19][20][21][22][23] a trend of the increased risk of symptomatic ICH after thrombolysis for ischemic stroke was noted if CMBs were present in pretreatment MRI. In our study, no new symptomatic acute stroke or ICH occurred, even with new CMB development.…”
Section: Discussionmentioning
confidence: 99%
“…Microbleeds in the brain are detected in conditions such as microangiopathy, Moyamoya disease, vasculitis, and posterior reversible encephalopathy syndrome [2]. Meanwhile, Thurnher et al [3] reported diffuse microsusceptibility changes, including in the brainstem and cerebellum, in critically ill immunocompromised patients undergoing mechanical ventilation and oxygenation.…”
Section: Images In Neurocritical Carementioning
confidence: 99%